Smart braille / Mohd Amer Farhan Kamarudin - Kamarudin, Mohd Amer Farhan (2019)
The analog phone are the early smartphone that used button for typing and control. There is a familiar button layout that can be remembered while used it. Now, the smartphone no longer have buttons, just a flat screens that need a little touch to work. This causes, difficulty for blind people to use smartphone. Then smart braille has been introduced. That device has been manufactured for the blind but that device was so expensive and some people cannot affordable to have it. This smart braille project are to make the device that more practical to blind people and also to reduce the cost of this device as opposed to existing ones for the blind people capable to have it. Arduino Uno has been used as microcontroller to control their display and the input. In this system, dot for braille code will appear to display for show an alphabet in braille code and user can key-in braille code by push the button same as the braille code. User can communicate with others using this project. This project used NodeMCU to send message to telegram.